Customer satisfaction: a study of home-based fashion entrepreneurs and custom-made garments - Homela, Chevllin (Vaal University of Technology, 2022)
Customer satisfaction has proven to be a major determinant on the success or failure of a business. Regrettably, fashion entrepreneurs are not meeting customer expectations because they have problems that are affecting the quality of their work. In order to promote customer satisfaction, fashion entrepreneurs require a master plan that is customer-based. Thus, they could implement customisation of garments to address customers’ concerns. It is, therefore, crucial for home-based fashion entrepreneurs to be aware of their customers’ needs and the factors that affect their satisfaction to boost its levels. Based on this background, it was found necessary to conduct a research study with the aim to determine factors that affect customer satisfaction of custom-made garments produced by home-based fashion entrepreneurs in the Emfuleni Local Municipality. A qualitative study, applying purposive and snowball sampling techniques, was conducted by means of one-on-one interviews. Data saturation guided the study and was reached after nineteen women were interviewed and two more interviews were done to enhance credibility. Analysis of data was conducted applying the six stages of Creswell’s approach of data analysis. During this process four themes emerged and were presented in line with their categories. The study findings revealed that some of the factors that largely influenced customer satisfaction were service quality, product quality, price, value and location. Garment fit and uniqueness were also found to be reasons why participants opted for custom-made garments. However, some of the participating women did not get the satisfaction they were seeking. Their satisfaction was negatively affected by garment quality, lack of communication, missing delivery deadlines and inaccessibility of the entrepreneur. The research outcome provides home-based fashion entrepreneurs with useful information to improve the levels of customer satisfaction.
M. Tech. (Department of Visual Arts and Design: Fashion, Faculty of Human Sciences), Vaal University of Technology.
Keywords: Customer satisfaction; Fashion entrepreneurs; Custom-made garments; Entrepreneurs; Dissertations, Academic -- South Africa.; Fashion merchandising -- South Africa.; Entrepreneurship -- South Africa.; Custom-made clothing.; Home-based businesses.